Advances in targeted therapies and new promising targets in esophageal cancer - Belkhiri, Abbes (Oncotarget, 2015)
Esophageal cancer, comprising squamous carcinoma and adenocarcinoma, is a leading cause of cancer-related death in the world. Notably, the incidence of esophageal adenocarcinoma has increased at an alarming rate in the Western world. Unfortunately, the standard first-line chemo-radiotherapeutic approaches are toxic and of limited efficacy in the treatment of a significant number of cancer patients. The molecular analysis of cancer cells has uncovered key genetic and epigenetic alterations underlying the development and progression of tumors. These discoveries have paved the way for the emergence of targeted therapy approaches. This review will highlight recent progress in the development of targeted therapies in esophageal cancer. This will include a review of drugs targeting receptor tyrosine kinases and other kinases in esophageal cancer. Additional studies will be required to develop a rational integration of these targeted agents with respect to histologic types of esophageal cancer and the optimal selection of cancer patients who would most likely benefit from targeted therapy. Identification of AURKA and AXL as key molecular players in esophageal tumorigenesis and drug resistance strongly justifies the evaluation of the available drugs against these targets in clinical trials.